Right atrial mass in a patient with COVID‐19 pneumonia: A case report - Fahmi Othman (14777506) (2023)
Lipomatous hypertrophy of the interatrial septum can have an atypical appearance by transthoracic echocardiography. The authors emphasize on the importance of the multimodality imaging approach to reach the appropriate diagnosis in such cases. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4220